The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1002/app.24629
|View full text |Cite
|
Sign up to set email alerts
|

Use of radiation grafting of polyethylene‐coated polypropylene nonwoven fabric by acrylamide for the removal of heavy metal ions from wastewaters

Abstract: The graft copolymerization of acrylamide (AAm) monomer onto polyethylene-coated polypropylene (PE-co-PP) nonwoven fabric was carried out by the mutual irradiation method. The general peculiarities of the grafting have been studied by gravimetric, scanning electron microscope (SEM), mechanical properties, and Fourier transform infrared (FTIR) methods. The influence of absorbed dose, dose rate, as well as the monomer concentration on the degree of grafting has been determined. Metal ions uptake of Cu 2þ , Co 2þ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Characteristic absorption peak of CMC and GA appeared at 3500 cm -1 for the hydroxyl groups (Silverstein and Webster 1998;Senna et al 2001). In the spectrum of unirradiated spectra there are bands at 2915, 1463 and 719 cm -1 , responsible for deformed vibration of CHgroups (Ibrahim et al 2006) as shown in these figures. In these figures there was new bands around 1700 cm -1 due to C=O absorption characteristic of COOH group of 100% CMC and 80% CMC in the unirradiated and irradiated spectra.…”
Section: Ft-ir Spectroscopic Analysismentioning
confidence: 84%
“…Characteristic absorption peak of CMC and GA appeared at 3500 cm -1 for the hydroxyl groups (Silverstein and Webster 1998;Senna et al 2001). In the spectrum of unirradiated spectra there are bands at 2915, 1463 and 719 cm -1 , responsible for deformed vibration of CHgroups (Ibrahim et al 2006) as shown in these figures. In these figures there was new bands around 1700 cm -1 due to C=O absorption characteristic of COOH group of 100% CMC and 80% CMC in the unirradiated and irradiated spectra.…”
Section: Ft-ir Spectroscopic Analysismentioning
confidence: 84%
“…The results observed are given in Figure 6. In the spectrum of unmodified fabrics there are bands at 2915, 1463, and 719 cm −1 , responsible for deformation vibrations of CH‐ groups9 as shown in Figure 6(a). Figure 6(b) shows IR spectrum of modified fabric in which there was new bands around 1700 cm −1 due to CO absorption characteristic of the COOH group.…”
Section: Resultsmentioning
confidence: 99%
“…The required dose was obtained by adjusting the electron beam energy parameters and conveyor speed. The dose being used was 30 kGy 9. The coating percent of modified fabric was calculated according to eq.…”
Section: Methodsmentioning
confidence: 99%
“…The nonwoven fabric PP/PE as an adsorbent was used to adsorb metals such as Cu (II), Ni(II), Co (II) with acrylamide as a monomer. The gamma radiation at a dose of 20-30 kGy was applied in the experiments 29 .…”
Section: Fig1mentioning
confidence: 99%